Facial markers in second‐ and third‐trimester fetuses with trisomy 18 or 13, triploidy or Turner syndrome. (1st June 2015) - Kagan, K. O.; Sonek, J.; Berg, X.; Berg, C.; Mallmann, M.; Abele, H.; Hoopmann, M.; Geipel, A.
ABSTRACT Objective To examine the effectiveness of nasal bone (NB) evaluation (including NB length (NBL)), prenasal thickness (PT) measurement, the PT:NBL ratio and the prefrontal space ratio (PFSR) in the identification of fetuses with trisomy 18 or 13, triploidy or Turner syndrome. Methods This was a retrospective study using stored midsagittal two‐dimensional images of the facial profile of fetuses with trisomy 18 or 13, triploidy or Turner syndrome in the second and third trimesters. For images of acceptable quality, measurements were obtained of NBL (where NB was present), PT, the PT:NBL ratio and PFSR, and these measurements were compared with previously published normal ranges. Results The search of databases identified 189 fetuses that met the study criteria: 132 (69.8%) with trisomy 18, 40 (21.2%) with trisomy 13, 10 (5.3%) with triploidy and seven (3.7%) with Turner syndrome. The NB was either absent or its measurement was below the 5th centile in 67 (50.8%), 20 (50.0%), five (50.0%) and two (28.6%) of the fetuses with trisomy 18, trisomy 13, triploidy and Turner syndrome, respectively. The PT measurement was above the 95th centile in 24 (18.2%), six (15.0%), one (10.0%) and one (14.3%) of the affected fetuses, respectively. The PFSR was abnormal in 72 (54.5%), 29 (72.5%), seven (70%) and four (57.1%) of the cases and the PT:NBL ratio was above the 95th centile or the nasal bone was absent in 72 (54.5%), 20 (50.0%), six (60.0%) and four (57.1%) cases, respectively. Conclusion Although each of the facial markers considered provides some useful information in screening for trisomy 18, trisomy 13, triploidy and Turner syndrome, the performance of none of the markers appears to be as good as that in screening for trisomy 21. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.